Disturbances of cardiac rhythm and conduction in familial amyloidosis with polyneuropathy. Issue 6 (June 1984) - Eriksson, P; Karp, K; Bjerle, P; Olofsson, B O
Abstract : Sixteen consecutive patients with familial amyloidosis with polyneuropathy of varying duration and severity underwent 24 hour ambulatory electrocardiographic monitoring. A high incidence of sinus node dysfunction, supraventricular and ventricular arrhythmias, and disturbances of atrioventricular conduction was found. Considerably more arrhythmias and disturbances of conduction were detected by long term electrocardiographic monitoring than by conventional 12 lead electrocardiograms. During a follow up period of three to 14 months five patients needed treatment by a pacemaker, three of them because of symptomatic complete heart block, one because of second degree heart block with heart failure, and one because of symptomatic dysfunction of the sinus node. The tachyarrhythmias did not require specific treatment. Long term electrocardiographic monitoring is a useful adjunct in the evaluation of patients with familial amyloidosis with polyneuropathy as it may detect otherwise unrecognised symptomatic disturbances of heart rhythm. The results may be valid also for other forms of amyloidosis involving the heart.